Nest takeover by queen and its positive impact on colony development in the Japanese bumblebee Bombus ignitus (Apidae: Hymenoptera). Issue 3 (17th January 2018) - Matsuyama, Hinako; Ono, Masato
Abstract: Lone Bombus ignitus queens are known to start nests in small underground cavities. To examine the nest‐site preference of post‐hibernating queens, choice tests were carried out by providing queens with orphan colonies and empty cavities as possible nesting sites within an experimental box. Our results showed that the queens had a strong preference for takeover of an orphan colony, suggesting that nest takeover (usurpation) could occur in nature even with the presence of possible empty cavities for nesting. We compared the colony‐growth process and final production of sexuals between non‐takeover and takeover colonies. The increase in the number of egg cups was faster in the takeover colonies, suggesting that orphan broods elicit earlier oviposition by the usurping queen. Reproductives emerged earlier (significant for new queens) and in greater numbers (males) from takeover colonies than from non‐takeover colonies. Thus, post‐hibernating B. ignitus queens would search for and take over small orphan colonies to increase their fitness. Abstract : To examine the nest‐site preference of post‐hibernating Bombus ignitus queens, choice tests were carried out by providing queens with orphan colonies and empty cavities as possible nesting sites within an experimental box. Although lone B. ignitus queens are known to start a nest in a small underground cavity, our results showed that the queens had a strong preference for takeover of an orphan colony. The increase in the number of egg cups was faster in the takeover colonies, and reproductives emerged earlier and in greater numbers from takeover colonies than from non‐takeover colonies.